Ocean modeling with flexible initialization for improved coupled tropical cyclone-ocean model prediction. (May 2015) - Yablonsky, Richard M.; Ginis, Isaac; Thomas, Biju
Abstract: This paper introduces the Message Passing Interface Princeton Ocean Model for Tropical Cyclones (MPIPOM-TC), created at the University of Rhode Island (URI). MPIPOM-TC is derived from a combination of the parallelized version of the Princeton Ocean Model (POM), called the Stony Brook Parallel Ocean Model (sbPOM), and URI's non-parallelized POM for Tropical Cyclones (POM-TC), which has been used for many years as the ocean component of NOAA's and the U.S. Navy's operational hurricane forecast models. In addition to parallelization, the flexible initialization capabilities of MPIPOM-TC and other elements of its architecture will facilitate further improvements to the ocean component of research-based and operational tropical cyclone (hurricane) forecast models worldwide. Graphical abstract: Highlights: MPIPOM-TC is a new, parallelized ocean model that merges POM-TC and sbPOM. MPIPOM-TC has flexible initialization options and worldwide regional domains. MPIPOM-TC can be used for both research-based and operational hurricane prediction. MPIPOM-TC can be configured and initialized for both real and idealized hurricanes. MPIPOM-TC can be configured with full 3-D dynamics or simplified 1-D dynamics.